2017
DOI: 10.1021/acs.orglett.7b02512
|View full text |Cite
|
Sign up to set email alerts
|

Tandem [3 + 2] Cycloaddition/1,4-Addition Reaction of Azomethine Ylides and Aza-o-quinone Methides for Asymmetric Synthesis of Imidazolidines

Abstract: An enantioselective synthesis of biologically important imidazolidines has been achieved via a tandem [3 + 2] cycloaddition/1,4-addition reaction of azomethine ylide and aza-o-quinone methides. With the use of this tool, various imidazolidine derivatives are obtained in good yields with excellent diastereoselectivities and enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…[32] Furthermore, Guo and coworkers reported a silver(I)catalyzed synthesis of imidazolidines 58 from aza-o-QM precursors 56 and azomethine ylides 57 (2 equivalents) as shown in Scheme 11. [33] In this method, an equivalent of silveractivated azomethine ylide 57 undergoes [3 + 2] cycloaddition with the other equivalent of 57 to form imidazolidine intermediates. The subsequent capture of the in situ formed aza-o-QMs by the imidazolidines via 1,4-addition produces the desired products 58.…”
Section: Transition-metal Catalysismentioning
confidence: 99%
“…[32] Furthermore, Guo and coworkers reported a silver(I)catalyzed synthesis of imidazolidines 58 from aza-o-QM precursors 56 and azomethine ylides 57 (2 equivalents) as shown in Scheme 11. [33] In this method, an equivalent of silveractivated azomethine ylide 57 undergoes [3 + 2] cycloaddition with the other equivalent of 57 to form imidazolidine intermediates. The subsequent capture of the in situ formed aza-o-QMs by the imidazolidines via 1,4-addition produces the desired products 58.…”
Section: Transition-metal Catalysismentioning
confidence: 99%
“…Although these motifs are lucrative both industrially and pharmaceutically, their synthesis advancement is very limited. A commonly implemented direct method for the synthesis of imidazolidine motif includes the 1,3-dipolar cycloaddition reaction , and condensation of 1,2-diamines with aldehydes, ketones, or oxo-compounds (Scheme a) . However, these processes are associated with the prefunctionalization of substrate and the use of expensive ligands .…”
Section: Introductionmentioning
confidence: 99%
“…As we know, a [4 + 2] cycloaddition reaction is among the most efficient approaches to access six-membered N -heterocycles via multiple bond formations in one pot, which usually features atom-economic reactions and improves the synthetic efficiency. , Recently, ortho -quinone methides ( o -QMs) and aza- ortho -quinone methides (ao-QMs) have attracted great attention in organic synthesis . As very reactive intermediates, they serve as general electrophiles to react with the nucleophiles to afford either [4 + n ] cycloaddition or 1,4-addition products through concerted or stepwise pathways . The [4 + 2] cycloadditions of o -QMs and ao-QMs with alkyl enolates and enamines have been explored extensively as a powerful and effective strategy to prepare benzopyran and tetrahdyroquinoline cores in organic synthesis (Scheme A). , For example, in 1999, Corey and co-workers first employed ao-QMs as useful synthons to form a series of hydroquinoline derivatives through intermolecular aza-Diels–Alder reactions, in which they found that the cycloaddition of ao-QMs with 2,3-dihydrofuran afforded tetrahydrofuro­[2,3- b ]­quinoline scaffolds (Scheme B) .…”
Section: Introductionmentioning
confidence: 99%